Vocabulary in English Language Learning, Teaching, and Testing in Vietnam: A Review - Duy Van Vu; Elke Peters (MDPI AG, 2021)
This review paper aims to provide an overview of vocabulary in English language learning, teaching, and testing in Vietnam. First, we review studies on the vocabulary knowledge of Vietnamese EFL learners. Recent research evaluating different aspects of vocabulary knowledge shows that Vietnamese EFL learners generally have limited knowledge of both single words and formulaic language. Next, we discuss contemporary approaches to teaching vocabulary in Vietnam to reveal current issues and provide relevant recommendations. Empirical studies on Vietnamese EFL learners' vocabulary acquisition are also discussed with an aim to shed light on how vocabulary can be acquired by Vietnamese EFL learners and subsequently draw important pedagogical implications. In addition, we look into the lexical component of high-stakes English tests in Vietnam, calling for more attention to the lexical profiles and lexical coverage of those tests. Finally, we provide concluding remarks and research-informed recommendations for EFL vocabulary learning and teaching in Vietnam to elaborate on how vocabulary can be effectively learned and taught.